The contribution of the Gaza Envelope Region to Israel's food security - Avraham Ben-Sheleg; Natalie De Falco; Uri Roll; Shimon Rachmilevitch (BMC, 2024)
Abstract Background Armed conflicts can severely impact food security by displacing farmers, destroying farms and agricultural infrastructure, disrupting supply chains, and limiting governance control over highly volatile food markets. In this study, we aim to gain an initial understanding of the impact of the ongoing Israel-Hamas War on local food production in Israel. Methods This study examined the challenges of food production in the Gaza Envelope region, a border area in Israel that has been profoundly affected by the recent conflict. The analysis focused on the allocation of land to specific agricultural crops and sectors, along with the nutritional output of these edible crops. The nutritional output was standardized based on the dietary needs of the Israeli population, considering population size and demographic factors. These methods aimed to understand the effects of conflict on crop diversity, the risks posed to specific crops, and the implications for nutritional security. Results We found that the Gaza Envelope region is crucial for the propagation of several key crops, notably cherry tomatoes, radishes, and sweet potatoes. We identified 16 crops whose local production is particularly vulnerable due to their proximity to the conflict, including radishes and potatoes. The nutritional output of the edible crops from the Gaza Envelope region is extensive, producing over 50% of the annual caloric requirements of the Israeli population. Beyond the caloric contribution, the produce from the region is nutrient-dense, supplying more than 100% of the annual Dietary Reference Intakes for the Israeli population of 12 vital nutrients, which include dietary fiber, six vitamins such as Vitamin A, Vitamin C, and Vitamin K, and five minerals including potassium and iron. These findings suggest that the Israel-Hamas War is having detrimental ramifications on local food production in Israel. Conclusions The ongoing conflict highlights the critical need for data informed agricultural support and policy adjustments to protect food production in conflict-affected areas. Up-to-date and accurate land use data are essential to assess the initial impact of any disaster swiftly and reliably on these zones. This approach will enable more effective responses to safeguard food security under crisis conditions.